Performance-related differences in the anaerobic contribution of competitive freestyle swimmers - Troup, J. P.; Hollander, A. P.; Bone, M.; Trappe, S.; Barzdukas, A. P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The purpose of this project was to determine (1) how the anaerobic energy contributions of competitive swimming distances may vary with performance level, and (2) whether the adjustment in 0) uptake to maximal swimming intensities are different between high vs low performance level swimmers. Based on 200 m freestyle performances, well trained swimmers were divided into two groups, (a) low performers (LP) (n = 30) 1.58 ± 0.02 mls and (b) high performance (HP) (n = 34) 1.69 ± 0.02 m/s. A swimming economy test was completed by all swimmers from which the 02 demand was determined corresponding to 100, 200 and 400 m work intensities. Each swimmer returned to the laboratory on separate days to complete swims at these prescribed intensities. During the swims expired gases were collected continuously on line with accumulated 0 uptake determined at 10 s increments. The 02 deficit was calcuiated as the difference between the 02 demand and the accumulated 02 uptake and used to describe the anaerobic capacity and the percent anaerobic energy contribution. Prior to the start and following each swim a mixed arterialized blood sample was collected for analysis of base excess, pH, lactate and buffer capacity. From the accumulated 02 uptake curves, the time to reach 25% of the total 0 demand was determined. Analysis of variance with repeated measufes was carried out to determine significance at P < 0.05. Results suggest that at the same relative work intensity, (1) anaerobic capacity varies with performance level, (2) anaerobic energy contributions differ with performance level and (3) swimmers of higher performance levels adjust to work at faster rates.